Effect of mHealth Communication on Modifiable Risk Factors of Non-Communicable Diseases in An Adult Rural Population of District Gautam Buddha Nagar, Uttar Pradesh - Makhija, Ankita; Srivastava, Shalini; Mahajan, Harsh; Juneja, Khushboo (National Journal of Community Medicine, 2025)
Introduction: Non-communicable diseases (NCDs) are responsible for 74% of all deaths globally. Burden of NCDs can be reduced by decreasing the modifiable risk factors associated with these diseases through behavioural change which can be done by the use of mHealth communication. Objectives: To assess the effect of mHealth communication on modifiable risk factors in an adult rural population of District Gautam Buddha Nagar, Uttar Pradesh. Methodology: A Community-based Interventional study was conducted among 480 adult subjects in the rural area of District Gautam Buddha Nagar, Uttar Pradesh. Baseline information on sociodemographic variables, behavioural risk factors (STEP 1), anthropometric and physiological risk factors (STEP 2), and biochemical risk factors (STEP 3) of NCDs was collected. mHealth intervention in the form of telephone calls and text messages was carried out for reduction of NCD risk factors following which post-intervention data of the risk factors was collected. Results: After mHealth intervention, significant reduction in tobacco use, alcohol use, unhealthy diet, physical inactivity, BMI, waist hip ratio, blood pressure, fasting blood sugar, total cholesterol, total triglyceride and low-density lipoproteins was observed in intervention group with respect to control group. Conclusion: Effect of mHealth communication contributed significantly to decrease majority of the modifiable risk factors of NCDs.